The Death of Amateurism in United States Collegiate Athletics - Heller, Thomas (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Collegiate athletics, especially men’s football and basketball, are extremely popular in the United States. As part of the cultural fabric of the country, these spectator sports have generated billions of dollars annually, far surpassing revenue generated in other major American sports leagues and even Premier League football in England. All those connected with these sports, including athletic directors, coaches, the National Collegiate Athletic Association – which is the governing body – athletic apparel companies, media outlets, etc. have profited from these sports. Everyone that is except for the athletes themselves. Historically, the athletes were considered amateurs and if they received any compensation, they lost their ability to participate in collegiate sports. Recently, in response to a barrage of lawsuits, the federal courts, including the Supreme Court, have held those rules that violated the Sherman Antitrust Act. As a result of these rulings, and legislation passed in most states, college athletes are now able to profit from their names, likenesses and images without losing their amateur status. And as a result of settlements in the litigation college athletes are now also receiving other compensation. The article traces these developments from their inception to the present time.